Utilization of palm solid residue as a source of renewable and sustainable energy in Malaysia - Wahid, Mazlan Abdul (Elsevier, 2014)
Today, global energy consumers are addicted to fossil fuels such as natural gas, oil and coal. Although it has been anticipated that fossil fuels will be depleted soon, these fuels are still dominant as the primary source of energy in the world. Recently, many efforts have been done to substitute renewable alternative fuels to reduce dependency on fossil fuels. Biomass as one of the earliest energy sources appears to be the most promising renewable energy source due to its numerous resources and its environmentally sound characteristics. Since Malaysia is agriculture based tropical country, many crops such as palm, paddy rice and sugarcane are cultivated in this region. Malaysian palm oil industry generate huge amounts of palm solid residue (PSR) biomass such as empty fruit bunches (EFB), palm fiber, shell, trunks and fronds as byproducts which are capable to be taken into account in the energy mix of the country. In this paper, an overview of the PSR generation from Malaysian palm oil industries and its social and economic effects has been given. Indeed, performance of the direct combustion of PSR in terms of PSR composition, properties, heating value, emissions and its effects on the equipment or the components of the boilers have been reviewed. It has been found that the very high moisture content of PSR of palm industry makes their collection and transportation expensive, therefore energy conversion process could be inefficient and utilization of these materials inside the palm oil mills seems more beneficial.